Analgesic Medicinal Plants in Shahrekord, Southwest of Iran: An Ethnobotanical Study: - Basati, Gholam; Abbaszadeh, Saber; Teimouri, Hassan; Zebardast, Arqavan (Galen Medical Journal, 2019)
Background: Identification of indigenous medicinal plants, including the gathering of information regarding the uses of these plants can help find out their traditional pharmacological activities and their benefits for the community’s healthcare system. In this study, an ethnobotanical investigation was conducted in Shahrekord city, southwest of Iran to indicate the ethnobotanical knowledge about analgesic medicinal plants in the region and the methods of using them. Materials and Methods: To this end, plant antioxidants and analgesic medicinal plants were identified. For this purpose, a questionnaire was used to obtain indigenous knowledge from traditional therapists in Shahrekord regarding pain relief using medicinal plants. This ethnobotanical study was conducted in 2018 with the participation of 29 traditional therapists of the region under purpose. Finally, the data drawn from the questionnaires were analyzed using the Excel software. The frequency of plants use was also calculated. Results: Our study showed that in Shahrekord, 23 species of medicinal plants are used to relieve pain. The highest frequency of use was obtained for Eugenia caryophylata (44%), followed by Alhagi maurorum (31%), Tribulus terrestris (27%), and angustifolia (24%). The Laminaceae family (7 species) was the most frequently used plant family for pain relief. The most frequently used plant organ to relieve the pain was flower (25%), followed by the stem (22%) and leaves (19%). Conclusion: Given the high importance of medicinal plants in Shahrekord, the results of this study and additional scientific investigations can help produce more effective and less harmful drugs from medicinal plants. [GMJ.2019;8:e1593]